Senegalese Professors’ Intention to Engage in Learner-Centered Instructional Strategies in Agriculture Courses - James C. Anderson II; Ibukun D. Alegbeleye; Wangui C. Gichane; Azenegashe O. Abaye (Journal of International Agricultural and Extension Education, 2019)
The Senegalese agricultural sector suffers from an inadequate number of skilled workers. On January 24, 2011, the United States Agency for International Development (USAID) launched the Education and Research in Agriculture (ERA) project to increase the number of skilled workers entering the agriculture supply pipeline. To achieve this goal, ERA provided professors with materials, resources, and the knowledge for incorporating learner-centered strategies in their curriculum. The purpose of this study is to describe the intentions of Senegalese agriculture professors in engaging in learner-centered instructional strategies. The theoretical framework guiding this study is Ajzen’s (1991) Theory of Planned Behavior, which identifies predictors that leads to an individual’s intention to engage in a certain behavior. Data were collected using survey questionnaire. Agriculture professors (n = 40) from three public universities and two training institutes affiliated with the universities completed the survey questionnaire. Purposive sampling was used to select professors from schools that had close involvement with the USAIDERA project. Findings suggest that Senegalese professors are engaging or intend to engage in a few learner-centered (LC) instructional strategies; have a positive attitude but still suffer from cognitive dissonance; have some challenges with subjective norms; and lack adequate selfefficacy that is necessary for engaging in LC instructional strategies. Continuous trainings that delineate the positive outcomes of engaging in LC instructional strategies is recommended to resolve the cognitive dissonance that many still have. We recommend future studies to investigate the degree of influence as measured by attitude, subjective norms, and perceived behavioral control.
Keywords: Senegalese professors; higher education; training and development; learner-centered instruction